Taking charge of professional development : a practical model for your school - Semadeni, Joseph H. (Alexandria, VA : ASCD, 2009)
A guide to professional development for teachers that discusses increasing morale, embracing new initiatives, instructional leadership, using resources, curriculum, assessment, systematic intervention, and differentiated instruction.
Inspiration to change -- Professional development -- Instructional leadership -- Use of resources -- Curriculum and assessment -- Systemic intervention -- Differentiated instruction -- Change through fusion.
Includes bibliographical references (p. 164-167) and index.
Professional
Keywords: Teachers -- In-service training; Teachers -- Professional relationships; Teachers -- In-service training